Hyperforin Ameliorates Imiquimod-Induced Psoriasis-Like Murine Skin Inflammation by Modulating IL-17A–Producing γδ T Cells - Zhang, Song; Zhang, Jia; Yu, Juanjuan; Chen, Xiaolu; Zhang, Fangyuan; Wei, Wei; Zhang, Lingyun; Chen, Wenmao; Lin, Nengxing; Wu, Yan (Frontiers in Immunology, 2021)
Hyperforin is a major active constituent of Hypericum perforatum L. extract, which is widely used for the treatment of depressive disorders. Recent studies have reported that hyperforin reduced inflammation in stroke and suppressed proliferation and differentiation in keratinocytes. Psoriasis is a chronic immune-mediated inflammatory skin disease in which the IL-23 / IL-17 axis plays an important role. To investigate the underlying inflammatory mechanisms and response of hyperforin in psoriasis, we use imiquimod (IMQ) – induced mice model, in vitro cultured murine splenic γδ T cells, and HaCaT cells in this study. Data showed that hyperforin reduced epidermal thickness and decreased IMQ-induced pathological scores of cutaneous skin lesions in mice. Meanwhile we proved that hyperforin suppressed infiltration of CD3+ T cells and downregulated expression of Il1, Il6, Il23, Il17a, Il22, antimicrobial peptides (AMPs) in the skin lesion. Hyperforin significantly inhibited imiquimod- induced splenomegaly, reduced serum levels of TNF-α and IL-6, and IL-17A in splenocytes and draining lymph nodes. Our study also suggested that hyperforin lessened the infiltration of γδ T cell and CCR6+ γδ T cells in spleen and lymph nodes. Hyperforin also suppressed the typical psoriasis-like inflammatory responses and the infiltration of IL-17A+ cells in dermal γδ T cells of IMQ treated Tcrd–/–mice transferred with γδ T cells. In vitro studies, hyperforin reduced the expression and secretion of IL-17A in γδ T cells, and suppressed the activation of MAPK/STAT3 pathways in human keratinocyte HaCaT cells and γδ T cells. In conclusion, hyperforin alleviates IMQ-induced inflammation in psoriasis through suppressing the immune responses exerted by IL-17 A-producing γδ T cells and related cytokines by modulating MAPK/STAT3 pathways. Our study provided a novel therapeutic tragedy for psoriasis by which hyperforin attenuates psoriasis-related inflammatory responses.